Indicators of the Russian Banking Sector in Modern Realities ("Journal "U". Economy. Management. Finance.", 2022)
The article is devoted to the analysis of indicators of the banking sector in Russia. Research objectives: a consideration of the indicators of the banking system in dynamics, an identification of problem areas, this sector development forecast. The importance of conducting a rational monetary policy for the stabilization of the banking sector and its further development is emphasized. The formulated conclusions make an additional contribution to a comprehensive study of the problem of the banking sector functioning.
Keywords: Banking sector; Bank of Russia; credit policy